Efficient plant regeneration through direct shoot organogenesis and two-step rooting in Eucommia ulmoides Oliver - Wang, Dacheng; Su, Pengfei; Gao, Yameng; Chen, Xue; Kan, Wenjie; Hou, Jinyan; Wu, Lifang (Frontiers in Plant Science, 2024)
Eucommia ulmoides Oliver (E. ulmoides Oliver), a multipurpose woody plant, holds great economic significance due to its expansive medicinal, food and industrial applications. The rapid advancement of E. ulmoides in various fields has resulted in the inadequacy of existing breeding methods to meet its growth and annual production demands. Consequently, there is an urgent need for innovative propagation strategies. This study introduces an optimized micropropagation protocol for E. ulmoides, facilitating direct shoot organogenesis from nodal segments with axillary buds. We systematically examined the impact of basal medium composition, plant growth regulators, photosynthetic photon flux density, and sucrose concentration on bud sprouting. Employing cuttings with axillary buds as propagation material, we achieved a shortened cultivation period of merely 4 weeks for bud elongation and proliferation, marking a substantial enhancement in propagation efficiency. Notably, the Driver Kuniyuki Walnut medium, supplemented with 20.0 g L−1 sucrose and 2.0 mg L−1 trans-zeatin, induced shoots sprouting with a 100% success rate and an average length of 5.18 cm per nodal segment, equating to a great bud propagation rate of approximately 500%. Furthermore, a light source with an intensity of 80 μmol m−2 s−1 was shown the most economical choice. To address the primary challenge of inducing roots in regenerated plants, we employed a refined two-step rooting technique. This method yielded the optimal rooting frequency of 93.02%, producing an average of 5.90 adventitious roots per plantlet, each with an average length of 2.77 cm. The micropropagation program developed in this work will be the cornerstone for the preservation of the germplasm of E. ulmoides and its long-term use in medicinal and industrial applications.